PENGARUH MACHIAVELLIAN DAN IDEALISME PADA PERSEPSI ETIS MAHASISWA AKUNTANSI - Ni Luh Budi Ariani; Ni Putu Ayu Kusumawati (UNHI Press, 2020)
Based on cases ofi ethical violations unwittingly form a reaction that becomes a perception ofi students in the profession in accounting. Perception is the attitude or opinion expressed to respond or give an interpretation of a phenomenom. This study aims to determine how the influence machiavelliani and idealism on the ethical perceptions ofi accounting students. This research was conducted at a private university in Denpasar. Datai collection is done by giving questionnaires tu students majoring in accounting at the faculty ofi economics ofi private universities. The study population numbered 302 peoples. Technique ofi determining samples using the Slovin formula. Datai analysis was performed by multiple linier regression analysis. The results ofi this study indicate that machiavelliani has a positive effect on the ethical perceptions ofi accounting students. Research result mean that the heigher the machiavelliani, the more ethical perceptions ofi accounting students will increase. While idealism have a negative effect on the ethical perceptions ofi accounting students, which means an idealistic individual will avoid various actions that can harm those around him.